State of fear : a novel - Crichton, Michael, 1942-2008. (New York : Avon, 2005)
In Paris, a graduate student in a secret laboratory reveals a powerful new technology to a beautiful and mysterious woman. A few hours later, the student is drugged and dumped in a river. Radical environmental terrorists are launching a fanatical campaign--and the very future of the world they seek to protect may be at stake. Only MIT scientist and federal agent John Kenner can stop the deadly plot before the terrifying consequences are realized--and millions die.
Originally published in hardcover: New York : HarperCollins, 2004.
Includes bibliographical references (p. [641]-672).
Keywords: Ecoterrorism -- Fiction; Submarines (Ships) -- Fiction; Global warming -- Fiction; South Pacific Ocean -- Fiction; Suspense fiction